CORRECTION - Eurasian Physical Technical Journal (Eurasian Physical Technical Journal, 2023)
CORRECTION to the article «RELATIONSHIP BETWEEN MAGNETIC PROPERTIES AND MICROSTRUCTURE OF FERRITES DURING SINTERING IN RADIATION AND RADIATION-THERMAL CONDITIONS» by Malyshev A.V., Lysenko Е.N., Sheveleva E.A., Surzhikova O.A., Aringazin A.K. The Original Article (https://phtj.buketov.edu.kz/index.php/EPTJ/article/view/78) was published on 2021-03-01 Eurasian Physical Technical Journal, 2021, Vol.18, No.1 (35), pp. 3 – 8. https://doi.org/10.31489/2021No1/3-8 with affiliations:1Tomsk Polytechnic University, Tomsk, Russia, malyshev@tpu.ru2Ceské vysokéucenítechnické v Prague, Prague, Czech Republic 3L.N. Gumilev Eurasian National University, Nur-Sultan, Kazakhstan 1)Authors name shood be read as:Malyshev A.V., Lysenko Е.N., Sheveleva E.A., Surzhikova O.A. 2)Affiliations shood be read as: 1Tomsk Polytechnic University, Tomsk, Russia, malyshev@tpu.ru2Ceské vysokéucenítechnické v Prague, Prague, Czech Republic